Quality control of homoeopathic medicines - Davey, R. William; McGregor, Julia A.; Grange, John M. (British Homeopathic Journal, 1992)
The stability of 55 mother tinctures stored under standard conditions over a twelve month period was estimated in terms of anti-bacterial activity against Pseudomonas aeruginosa, Bacillus cereus and Staphylococcus aureus. There was little change in activity over the period.
Keywords: Stability; Storage; Bioassay; Mother tinctures